1 - Deanship, Leadership Dilemmas and Management Challenges Facing the Social Sciences1 in Public University Education in Kenya - Kenneth Inyani Simala (Journal of Higher Education in Africa, 2014)
This paper stems from a sense of unease with the current leadership and management of Faculties of Social Sciences in Kenyan universities. Guided by the belief that social sciences must be judged by their sound scholarship and their policy relevance, the paper discusses dilemmas facing deans of these faculties in the execution of their leadership roles in overall university management. The paper is premised on the fact that the university sector in Kenya is experiencing unprecedented change in an effort to meet local obligations and respond to the global higher education agenda.